High-efficiency electrogeneration of hydrogen peroxide from oxygen reduction by carbon xerogels derived from glucose. (10th October 2019) - Liang, Liang; Zhou, Minghua; Lu, Xiaoye; Su, Pei; Sun, Jianhui
Abstract: Developing highly active and selective, and low cost electrocatalysts for the 2e − oxygen reduction from environmentally friendly precursors is attractive to industrial production and environmental remediation. In this study, carbon xerogels (CXs) were synthesized by the hydrothermal carbonization of glucose and polyaniline (PANI) and then used as catalysts for electrochemical generation of H2 O2 from O2 . It was found that the H2 O2 production performance could be easily tunable by polymerization temperature of PANI (0–80 °C), in which onset potential (−0.45 V to −0.29 V) decreased while the catalytic activity and H2 O2 selectivity (47%–94%) increased with the polymerization temperature. CX-80 (prepared at 80 °C) exhibited the best catalytic activity with excellent H2 O2 selectivity of 94% in neutral condition, better than most reported electrocatalysts. The H2 O2 production was also tested using gas diffusion electrodes modified by CXs, showing a high H2 O2 yield (5.1 mg h −1  cm −2 ) and stability with low energy consumption (7.2 kWh kg −1 ) at cathode potential of −1.0 V and pH 7. The excellent performance of CX-80 was attributed to large volume of meso-/macropores and high content of C=O. We believed that CX-80 would be a promising metal-free electrocatalyst for sustainable and in-situ H2 O2 generation from O2 in energy and environmental fields. Graphical abstract: Image 1 Highlights: Glucose-derived carbon xerogels (CXs) were synthesized for electrogenertion of H2 O2 . Effect of polymerization temperature on electrosynthesis of H2 O2 was investigated. CX-80 exhibited an excellent H2 O2 selectivity of 94% in neutral condition. The activity of CXs was related to volume of meso-/macropores and content of C=O.